Pantera Negra y Shang Chi la influencia de su pasado cultural en la construcción del personaje desde la dirección de arte - Garrido Sumarriva, Maria Belen (2022)
Films frequently present cultural representations of different countries, however, although there were cinematographic works that were considered as adequate interpretations of different ethnicities ("Do the Right Thing" (1989), "The Joy Luck Club" (1993), among others), there were several representations shown on screen that functioned as a way to mock a culture different from the American one, or to put Americans in a superior position to the rest. It is by considering that one form of representation can be given in relation to the visual aspect of the films, such as the costumes and locations in which the stories take place, that one thinks of how the good use of different details in terms of art direction can help to make a correct cultural representation through its contribution to the construction of the characters. The present research studies the costumes and scenography used in the films "Black Panther" and "Shang Chi", which are related to the main characters of both films. From different characteristics and indicators of both aspects of art direction, found through a content analysis, the research identifies key points that relate to cultural representation and assesses whether this type of representation moves away from or closer to the stereotypes posed in Hollywood films of the past. It is concluded that cultural representation is present in different ways in the films analyzed. Likewise, although different forms of allusions to a certain culture are seen, they are not excessively predominant. Rather, they are mixed with current aspects and aspects of other cultures, allowing the characters to be culturally correct and to continue to show themselves as global people capable of managing in different environments without having to abandon their original customs.